PERKEMBANGAN GEMEENTE BANJARMASIN DI KORAN BINTANG BORNEO TAHUN 1928 - Sofyana, Berliani; Marfuah, Siti; Jamil, Jamil (Amarthapura: Historical Studies Journal, 2023)
In the context of implementing Decentralisatie Wet 1903, the Dutch government issued Decentralisatie Besluit 1905 and Local Raden Ordonnantie. In Decentralisatie Besluit, the main points of formation, composition, position and authority of the council (Raad) in matters of financial management are separated from the central government. Meanwhile, the Local Raden Ordonnantie is an implementing regulation that regulates the structure, status and authority of the council (Raad), especially Gewestelijke Raad, Plaatselijk Raad, and Gemeenteraad. Gemeente Banjarmasin is a term in Dutch which means "municipality" or "regional government of Banjarmasin, Indonesia". Gemeente Banjarmasin is an administrative entity that regulates the territory and various aspects of Banjarmasin city government.